Yield Curves in the Post-LIBOR World - Brun, Victor (My University, 2023)
The transition from the forward-looking LIBOR to backward-looking rates such as SOFR presents a modelling challenge, as the widely used LIBOR Market Model (LMM) is designed for forward-looking rates. To address this, the generalised Forward Market Model (FMM) has been proposed, capable of describing both forward-and backward-looking rates. In this thesis, we study the properties of the FMM, focusing on the differentiability of the yield to maturity curve implied by the Heath-Jarrow-Morton-fitted FMM. We investigate the non-differentiability of the yield to maturity curve, and show that it is heavily influenced by the choice of zero-coupon bond interpolation method.
Keywords: Interest rates, backward-looking rates, LIBOR, generalised forward market model, yield curve.